2023
DOI: 10.3201/eid2902.221243
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of SARS-CoV-2 Omicron BA.5 Infections, Macau, June–July 2022

Abstract: A SARS-CoV-2 Omicron BA.5 outbreak occurred in Macau from mid-June through July 2022. Out of >1,800 laboratory-confirmed cases, most were mild or asymptomatic; only 6 deaths were recorded. The outbreak was controlled through stringent public health and social measures, such as repeated universal testing and a stay-at-home order lasting 2 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…Quality assessment (Additional file 1 : Table S4 [ 9 , 10 , 12 , 13 , 21 , 22 , 26 – 32 , 34 , 37 40 , 42 – 60 , 62 – 65 , 67 – 71 , 73 , 74 , 76 , 78 – 86 , 89 , 90 , 92 – 94 , 97 – 99 , 101 – 107 , 109 – 115 , 117 121 , 123 – 128 , 130 , 131 , 133 , 136 – 139 , 141 – 153 , 155 – 161 , 164 – 166 ]) indicated that 1 study provided a precise exposure window for cases and identification of the potential infector(s). Sixty-eight studies included a well-characterized cohort of individuals that were comparable with the population and provided precise estimates for the symptom onset window for themselves and their potential infector(s).…”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment (Additional file 1 : Table S4 [ 9 , 10 , 12 , 13 , 21 , 22 , 26 – 32 , 34 , 37 40 , 42 – 60 , 62 – 65 , 67 – 71 , 73 , 74 , 76 , 78 – 86 , 89 , 90 , 92 – 94 , 97 – 99 , 101 – 107 , 109 – 115 , 117 121 , 123 – 128 , 130 , 131 , 133 , 136 – 139 , 141 – 153 , 155 – 161 , 164 – 166 ]) indicated that 1 study provided a precise exposure window for cases and identification of the potential infector(s). Sixty-eight studies included a well-characterized cohort of individuals that were comparable with the population and provided precise estimates for the symptom onset window for themselves and their potential infector(s).…”
Section: Resultsmentioning
confidence: 99%
“…For this study specifically, we chose individuals within each of the groups who had an HAI titer of <10 against the A/Hawaii/70/2019 (H1N1) vaccine strain prior to vaccination in year 1 (2020-2021); this criterion means that the study focuses on individuals with relatively low initial titers. None of the participants were infected with influenza during the study time frame because there was minimal influenza circulation at the study site in Hong Kong between the initial 2020-2021 blood draw and the 2021-2022 blood draws due to COVID-19 mitigation measures (27,28). We analyzed sera collected immediately before (day 0) and approximately 30 days after the participants were given the 2021-2022 vaccine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the parameter values of the SEIHR model were set by steps. Firstly, the awareness delay was assumed to be 2 days for Fuzhou COVID-19 large wave, because Omicron BA.5.2 variant was a highly infectious variant as studied in ( Duan & Jin, 2022 ; Huang et al., 2020 ; Huo et al., 2023 ; Nguyen et al., 2021 ; Xiong et al., 2023 ; Fuzhou Statistics Bureau, 2020 ). Then, the average lengths of hospitalization 1/ γ 2 k were calculated using the surveillance data from Fujian CDC.…”
Section: Methodsmentioning
confidence: 99%